Aspectos do desenvolvimento em feijão comum (Phaseolus vulgaris L.) inoculados com Trichoderma spp. - Moreira, Suya Samara (2014)
Fungi of the genus Trichodermaspp. can be used as biological control agents and also as inducer of growth in different plants. Its action is based on different mechanisms such as the production of secondary metabolites, competition for space and nutrients, production of hydrolytic enzymes and signaling molecules. However, only a few works were made about morphological and anatomical aspects of the interaction between Trichodermaspp. and plants. This project aims to watch and determine the effects of inoculation of Trichoderma harzianum(ALL42 and T22) and Trichoderma asperellum(T34) strains in morphological and anatomical aspects of the bean (Phaseolus vulgarisL.). Morphological parameters as size of the root, root volume, dry mass and leaf area were analyzed, and some anatomical parameters like quantitative analysis of mesophile thickness leaf epidermis in stages V2, V4, R5, R7and R8, and the alteration of the structural characteristics of the root in stages V2, V4 and R5. The treatments were performed in seeds free from inoculation with Trichodermaspp. (control) and seeds treated with Trichodermaspp. T 22, ALL42 and T34 with three replicates each, totaling twelve treatments for stage analyzed. Statistical analysis was performed by ANOVA analysis of variance and separation of means test. The obtained data suggest that changes occurred inthe biomass of the dried plant, leaf area, length and volume of the root in most of the analyzed stages. However, in thickness of mesophyle analyse, significant differences was found only in stages V4 and R7. It was observed that the treated samples showed a greater Trichodermaspp. secondary cylinder vascular growth of roots, mainly in V4 stage. Was observed in R5 stage a further development of secondary xylem in the vascular cylinder of roots when treated with Trichodermaspp.. These data suggest that the fungus accelerates the development in P. vulgarisL. roots. Among the parameters analyzed, isolates of T. harzianum(ALL42 and T22) was those who shows a bigger difference when compared with the control.